The macroeconomic effect of the information and communication technology in Hungary - Peter Sasvari (International Journal of Advanced Computer Science and Applications (IJACSA), 2011)
It was not until the beginning of the 1990s that the effects of information and communication technology on economic growth as well as on the profitability of enterprises raised the interest of researchers. After giving a general description on the relationship between a more intense use of ICT devices and dynamic economic growth, the author identified and explained those four channels that had a robust influence on economic growth and productivity. When comparing the use of information technonology devices in developed as well as in developing countries, the author highlighted the importance of the available additional human capital and the elimination of organizational inflexibilities in the attempt of narrowing the productivity gap between the developed and developing nations. By processing a large quantitiy of information gained from Hungarian enterprises operating in several economic sectors, the author made an attempt to find a strong correlation between the development level of using ICT devices and profitability together with total factor productivity. Although the impact of using ICT devices cannot be measured unequivocally at the microeconomic level because of certain statistical and methodological imperfections, by applying such analytical methods as cluster analysis and correlation and regression calculation, the author managed to prove that both the correlation coefficient and the gradient of the regression trend line showed a positive relationship between the extensive use of information and communication technology and the profitability of enterprises.
Keywords: M13; M15; 330; Economic sector; ICT; Profitability; Total Factor Productivity